The oxford handbook of the sociology of religion - Clarke, Peter B. (Oxford Oxford University Press, 2011)
The Oxford Handbook of the Sociology of Religion draws on the expertise of an international team of scholars providing both an entry point into the sociological study and understanding of religion and an in-depth survey into its changing forms and content in the contemporary world. The role and impact of religion and spirituality on the politics, culture, education and health in the modern world is rigorously discussed and debated.